Reaktualisasi Materi PAI dalam Analisa Sosio-Psikologis - Maimun, Maimun (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2019)
The Islamic religious education is always in the spotlight as the education system in Indonesia. It is couse of its strategic position in growing the emotional and spiritual maturity of students. Many facts,where the content of this matery is evaluated, show a different reality that ensures its minimal role and almost nonexistent. This condition makes it get more attention, especially by seeking sociological and anthropological studies in it. By using structural functionalism and humanism approaches, we get an understanding that Islamic religious education must be touched by a sociological and psicological perspective through material content, teachers, principals and school environments all of which are oriented to the broadest interests of humanbeing.